Comparison of Liquefaction Potential Analysis Methods Based on CPTu data on Reclamation Island, Pantai Indah Kapuk, DKI Jakarta, Indonesia - Rahman, Erfandi; Sadisun, Imam Ahmad; Dinata, Indra Andra (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Liquefaction analysis in reclaimed areas has been intensively conducted because reclamation materials are generally non-cohesive and susceptible to liquefaction. Indonesia, known as the “Ring of Fire,” has high seismic potential that can trigger liquefaction. The cone penetration test (CPT) is one of the methods used to obtain subsurface soil layer data, which are subsequently applied for liquefaction analysis and evaluation of the geological conditions of the study area. This study compares three currently developing methods for liquefaction analysis. The results of soil layer analysis in the study area indicate three variations of sediment types, namely sand, silt, and clay. The method proposed by Boulanger and Idriss (2014) yields FS values < 1 for materials with fines content (FC) greater than 30%, which are considered susceptible to liquefaction. In contrast, the Robertson (2009) method also produces FS values < 1 for materials with FC > 30%, while the method proposed by Moss et al. (2006) results in FS values > 1 for materials with FC < 30%. The comparison of the three methods generally shows that the study area has a high liquefaction potential in clean sand materials at depths ranging from 4.5 to 15 m below the ground surface.